PENGARUH METODE BERMAIN DALAM MENINGKATKAN PASSING ATAS BOLA VOLI KELAS VI DI SEKOLAH DASAR NEGERI KARANGSARI - Ridwan Afandi; Ahmad Syarif (STKIP Melawi, 2026)
Abstract: This study aimed to determine the effect of the play-based method on improving overhead passing skills in volleyball among sixth- grade students at SD Negeri Karangsari. The research employed a quasi- experimental design using a One Group Pretest–Posttest model. The subjects consisted of 20 students who participated in a pretest, play-based learning activities, and a posttest to measure skill development. The research instrument was the AAHPERD overhead passing test, which assessed accuracy and movement consistency. The results showed a significant improvement between pretest and posttest scores. Hypothesis testing using a Paired Sample t-Test produced a t-value of -63.803 with a significance level of 0.000. The mean score difference of -64.55 indicated that posttest scores were substantially higher than pretest scores. These findings demonstrate that the play-based method effectively enhances basic technical skills, motor abilities, coordination, focus, and students’ self- confidence, making it suitable for physical education learning aligned with children’s developmental characteristics. Keywords: play method, overhand passing, volleyball, physical education learning Abstrak: Penelitian ini bertujuan mengetahui pengaruh metode bermain terhadap peningkatan kemampuan passing atas bola voli pada siswa kelas VI SD Negeri Karangsari. Penelitian menggunakan desain eksperimen semu dengan model One Group Pretest–Posttest. Subjek penelitian berjumlah 20 siswa yang mengikuti tes awal, pembelajaran berbasis permainan, dan tes akhir untuk mengukur perkembangan keterampilan. Instrumen penelitian menggunakan tes passing atas AAHPERD yang menilai ketepatan serta konsistensi gerak. Hasil analisis menunjukkan adanya peningkatan signifikan antara nilai pretest dan posttest. Uji hipotesis melalui Paired Sample t-Test menghasilkan nilai t hitung sebesar -63,803 dengan signifikansi 0,000. Rata-rata perbedaan skor sebesar -64,55 menunjukkan hasil posttest lebih tinggi. Temuan ini membuktikan metode bermain efektif meningkatkan teknik dasar, kemampuan motorik, koordinasi, fokus, dan kepercayaan diri siswa, serta layak diterapkan dalam pembelajaran PJOK sesuai dengan karakteristik perkembangan anak sekolah dasar formal. Kata Kunci: metode bermain, passing atas, bola voli, pembelajaran PJOK